Neuroimmune Dysregulation in Schizophrenia: A Cross-Domain Systematic Review of Developmental, Genetic, and Systemic - Sarah Salsabil; Husna Adlin; Firdus Firdus; Rosnizar Rosnizar (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2026)
Schizophrenia affects approximately 1% of the global population. Dopaminergic models have long dominated pathophysiological accounts and the immune system is increasingly recognized as a mechanistically active contributor. However, no comprehensive synthesis of recent cross-domain neuroimmune evidence exists. This systematic review aimed to characterize the scope, quality, and clinical relevance of neuroimmune research in schizophrenia published between 2025 and 2026. Following PRISMA 2020 guidelines, Scopus was searched using 'schizophrenia' AND 'immune system,' yielding 1,497 records. After screening for publication year, document type, and full-text eligibility, 55 peer-reviewed articles were included across ten thematic domains. A convergent neuroimmune signature emerged: pro-inflammatory cytokines were consistently elevated and correlated with symptom severity; the neutrophil-to-lymphocyte ratio independently predicted PANSS scores, suicidal ideation, and hospitalization duration; gestational poly I:C-induced Maternal Immune Activation (MIA) programmed durable immune dysregulation in non-human primate offspring through late adolescence; transcriptome-wide Mendelian randomization identified 196 immune-cell schizophrenia risk genes, with IRF3 enrichment linking the disorder to antiviral pathways; and specific gut microbiota genera (Barnesiella, Desulfovibrio, Gordonibacter, and Romboutsia) exerted causal protective effects via immune-inflammatory mechanisms (OR 0.85–0.93). These findings establish schizophrenia as a disorder with a multifaceted neuroimmune signature spanning developmental, genetic, cellular, and systemic dimensions. The field has advanced from correlational observation to causal inference and therapeutic proof-of-concept, positioning the immune system as a critically underexplored target for next-generation psychiatric treatment and necessitating immune-stratified trial designs alongside routine immunological monitoring in clinical practice.